Flexural Behavior of the Layered Beams Containing Reactive Powder Concrete and Self-Compacting Concrete - Aseel Abdulazeez Abdulridha; Sura Amoori Abbas; Lubna Salim Danha; Zainab Hassan Shaker (Journal of Engineering and Technological Sciences, 2022)
Reactive powder concrete (RPC) possesses superior structural and mechanical characteristics. Despite these excellent properties, the main drawback of RPC is that it is a very costly material. This study included an experimental program for studying the flexural behavior of hybrid beams containing RPC together with self-compacting concrete (SCC) in the same section. Five specimens with dimensions of 100 x 150 x 1000 mm were investigated. The first crack load, ultimate load, maximum deflection, load-deflection response, and crack pattern were investigated. The experimental program included testing five reinforced concrete beams with four-point loading. The specimens were cast as follows: full depth of self-compacting concrete; full depth of reactive powder concrete; half of the section depth of RPC (tension zone); quarter of the section depth of RPC (tension zone); and half of the section depth of RPC (compression zone). The experimental results of the hybrid beams showed that using RPC in the tension zone of the beam significantly improved the performance of the hybrid beams when compared with the SCC beam. The improvement rate increased with the RPC layer thickness in the tension zone. Using RPC in the compression zone together with SCC did not produce a significant improvement in the performance of the hybrid beams.